RUSSIAN SCHOOL FOR BREASTFEEDING SUPPORT: IMPLEMENTATION OF A PARADIGM IN PRACTICE - V. I. Furtsev; М. Yu. Galaktionova ("Paediatrician" Publishers LLC, 2014)
Functional nutrition is one of the main factors ensuring infants' balanced growth and development, as well as learning abilities, immunity to unfavourable environment conditions during infancy period. It also provides for a morphofunctional development of infant organs and body systems, and ensures that an infant will grow up to his or her genetically determined age growth and development level. Choosing the proper nutrition for infants, one can prevent nutritional disorders, rickets, anaemias, acute infectious and non-contagious diseases. It can also reduce the probability of the development of chronic diseases, and allows to sustain relatively high quality of life of infants with congenital and genetic anomalies. Using breast milk as a primary source of nutrition is the most optimum choice of infant feeding. However, according to the statistical data, the numbers reported for occurrence and duration of breastfeeding in Russia are far from being perfect.